2013
DOI: 10.1002/grl.50344
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of peak electron density in the ionosphere of Mars on solar irradiance

Abstract: Previous studies of the Mars ionosphere have concluded that increased solar flux leads to increased peak electron densities. Many have described this relationship as Nm ∝ Fk, where Nmis the peak electron density, F, the ionizing flux, is represented by either F10.7 or E10.7, and k is an exponent. The derived exponents have varied greatly, but have a mean value of k ≃ 0.35. Here, we explore this relationship using solar spectra measurements from the TIMED‐SEE instrument and Mars Global Surveyor radio occultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…At Mars the dominating neutral species is CO 2 whose ionizing threshold is 90nm, while the dominant species in the atmosphere of Titan is N 2 , whose photoionization threshold is 79.6nm [ Schunk and Nagy , ]. The observational value of the power law exponent k was found to be 0.47±0.02 by Girazian and Withers [], in good agreement with theoretical predictions. We therefore follow their study and use the solar energy flux, in the range 1–80nm, for our proxy of the ionizing flux.…”
Section: Observationssupporting
confidence: 75%
See 2 more Smart Citations
“…At Mars the dominating neutral species is CO 2 whose ionizing threshold is 90nm, while the dominant species in the atmosphere of Titan is N 2 , whose photoionization threshold is 79.6nm [ Schunk and Nagy , ]. The observational value of the power law exponent k was found to be 0.47±0.02 by Girazian and Withers [], in good agreement with theoretical predictions. We therefore follow their study and use the solar energy flux, in the range 1–80nm, for our proxy of the ionizing flux.…”
Section: Observationssupporting
confidence: 75%
“…The data are obtained from the TIMED‒SEE website at LASP (lasp.colorado.edu/see/l3_data_page.html), and the ready routines (PLOT_SEE.PRO) that we use for extrapolating the data are available through that site. Note that the same data and the same routines have been used in a recent similar study for the Mars ionosphere, where similar results as in this paper were presented [ Girazian and Withers , ].…”
Section: Instruments and Coordinate Systemsmentioning
confidence: 55%
See 1 more Smart Citation
“…At higher altitudes, above ∼170–180 km, the ionosphere is no longer in photochemical equilibrium and the configuration is instead dictated by transport processes, giving rise to complex vertical structuring [ Shinagawa and Cravens , , ; Nagy et al , ; Kopf et al , ; Morgan et al , ; Němec et al , ]. It has been shown that the photochemical ionosphere responds to variations in insolation much as is to be expected from application of simple Chapman theory [ Breus et al , ; Morgan et al , ; Withers et al , ; Lillis et al , ; Němec et al , ; Zou et al , ; Girazian and Withers , ]. In contrast to Venus, Mars does not possess a sustained nightside ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…What is more evident in this dataset is the increase of the peak altitude with solar activity, especially at high solar zenith angle. Girazian and Withers (2013) propose an empirical relationship, with the maximum electron density varying as the square of F10.7. Sanchez-Cano et al (2015) used Mars Express radar data covering almost one solar cycle and analyzed differences in the shape of the topside electron density profiles.…”
Section: Variability Of the Upper Atmospherementioning
confidence: 99%